2023
DOI: 10.1186/s12906-023-03967-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of morroniside from Cornus officinalis sieb. Et zucc against Parkinson’s disease via inhibiting oxidative stress and ferroptosis

Abstract: Parkinson’s disease (PD) is the second most common neurodegenera­tive disorder after Alzheimer disease accompanied by the death of dopaminergic neurons and brain nigrostriatal mitochondrial damage in the elderly population. The features of the disease include tremor, rigidity, postural instability, and motor retardation. The pathogenesis of Parkinson’s disease is complex, and abnormal lipid metabolism resulting in ferroptosis due to the excessive accumulation of free radicals from oxidative stress in the subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Conversely, JWA knockdown amplified ferritinophagy, thereby inciting the Fenton reaction and facilitating ferroptosis. Interestingly, we found that both the mRNA levels of FTH / FTL and the protein level of FTH1 were reduced in the MPP + model, which may be attributed the decreased Nrf2 expression as reported previously [ 35 , 36 ]. However, JWA overexpression served to increase the protein level of FTH1, with no corresponding changes to the mRNA levels of FTH / FTL .…”
Section: Discussionsupporting
confidence: 86%
“…Conversely, JWA knockdown amplified ferritinophagy, thereby inciting the Fenton reaction and facilitating ferroptosis. Interestingly, we found that both the mRNA levels of FTH / FTL and the protein level of FTH1 were reduced in the MPP + model, which may be attributed the decreased Nrf2 expression as reported previously [ 35 , 36 ]. However, JWA overexpression served to increase the protein level of FTH1, with no corresponding changes to the mRNA levels of FTH / FTL .…”
Section: Discussionsupporting
confidence: 86%
“…SAL’s ability to upregulate this pathway was evident in A53T-α-syn-SH-SY5Y cells, where it alleviated ferroptosis and promoted cell survival. Related, the research suggests that Morningside can activate the Nrf2/ARE signaling pathway to increase antioxidant capacity, thereby inhibiting abnormal lipid metabolism and protecting dopaminergic neurons in PD from ferroptosis [ 29 ]. Additionally, Sun observed a protective effect against 6-OHDA-induced dopaminergic neuronal ferroptosis in zebrafish and SH-SY5Y cell models through the upregulation of the Nrf2 signaling pathway [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…SYXK (Zhe) 2021-0033). We utilized thirty-two 12-week-old male C57BL/6 mice according to the previous studies [ 28 , 29 ] for consistent progression of PD symptoms, each weighing approximately 25 g, procured from SLAC, Shanghai, China (License No. SCXK (Hu) 2017-0005).…”
Section: Methodsmentioning
confidence: 99%
“…GSH exists not only in the cytoplasm but also in mitochondria, and protects mitochondria from oxidative stress by scavenging ROS generated during electron transport and oxidative phosphorylation within mitochondria ( Jacobs and Riemer, 2023 ). Recently, Li et al . (2023) found that morroniside can reduce ROS production by restoring the mitochondrial respiratory chain in a Parkinson’s disease model.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that the anti-cytotoxic effect of morroniside in response to H 2 O 2 treatment was associated with preservation of SOD activity, inhibition of calcium (Ca 2+ ) accumulation, and blockade of mitochondrial membrane potential (MMP) reduction ( Wang et al ., 2009 ). Morroniside also prevented brain injury following focal cerebral ischemia by protecting oxidative stress and apoptosis ( Wang et al ., 2010 ), and was proven to have similar efficacy in models of Alzheimer’s ( Chen et al ., 2023 ) and Parkinson’s disease ( Li et al ., 2023 ). Recently, we reported that heme oxygenase-1 activation by morroniside plays a crucial role in minimizing oxidative and inflammatory damage in lipopolysaccharide-challenged macrophages ( Park et al ., 2021 ).…”
Section: Introductionmentioning
confidence: 99%